Preparation method and application of urea-based phenolic resin based on urea-formaldehyde waste glue depolymerization

Through the pre -treatment and rectification treatment of rigid formaldehyde resin waste gum, prepare the larvae phenolic resin, and apply it to the production of bamboo and wood plywood, solve the problem of treatment difficulties for the treatment of rigid formalum resin, and realize the use of resource utilization and environmental protection. Double benefits.

CN119331188APending Publication Date: 2025-01-21NAT FORESTRY & GRASSLAND ADMINISTRATION BAMBOO RES & DEV CENT
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411434561.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively treat waste urea-formaldehyde resin liquid, resulting in environmental pollution and waste of resources.

Method used

The urea-formaldehyde waste glue is processed through pretreatment, depolymerization and reactivation to obtain waste glue hydrolyzate, and the hydrolyzate is added during the phenolic resin synthesis process to prepare urea-formaldehyde resin, which is used in the production of bamboo plywood.

Benefits of technology

The resource and utilization of waste gums in rigidaldehyde resin is realized, reducing environmental pollution, reducing the cost of wastewater treatment, and improving the production efficiency of artificial boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331188A_ABST
    Figure CN119331188A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of forestry engineering, in particular to a preparation method and application of urea-based phenolic resin based on urea-formaldehyde waste glue depolymerization. The preparation method comprises the following steps: pretreating urea-formaldehyde waste glue, depolymerizing and reactivating to obtain a waste glue hydrolysate; the waste glue hydrolysate is added in the synthesis process of the phenolic resin to prepare the ureido phenolic resin. Aiming at the problem of treatment of the urea-formaldehyde resin waste glue solution, the invention combines the actual production of artificial board products, develops the reactivation process research of the waste glue solution to realize the resource utilization research of urea-formaldehyde resin, and has certain creativity. The invention aims at reducing the pollution of the waste glue solution to the environment, changing the urea-formaldehyde resin waste glue into wealth and realizing the green development of the artificial board industry. The research scheme has feasibility, the project has good application prospects, double economic benefits will be generated, and good ecological and social benefits are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of forestry engineering, and in particular to a preparation method and application of urea-based phenolic resin based on depolymerization of urea-formaldehyde waste rubber. Background Art

[0002] Urea-formaldehyde resin is one of the main types of glue used in the production of artificial boards. When mixing glue, flour, wood powder, curing agent and other additives are added to improve the initial viscosity and ensure the bonding strength. During the process of gluing and molding artificial boards, about 2-5% of urea-formaldehyde resin glue waste glue is generated, and a large amount of urea-formaldehyde resin waste glue is also generated during equipment cleaning and process adjustment. At present, there are two ways to treat waste glue. First, sawdust is added to the waste glue, and it is naturally solidified into glue blocks and then burned. The invention patent of Chen Jincai et al. discloses an adhesive waste glue incineration treatment device, which can reduce the generation of waste residue by circulating the waste glue. However, the incineration treatment will produce a large amount of harmful gases, and the waste glue liquid will produce odor due to the fermentation of flour balls and other additives during the natural solidification process, causing air pollution. At the same time, the waste glue blocks are hazardous solid wastes and need to be entrusted to the environmental protection department for unified disposal. The market price of the waste glue liquid hazardous waste for environmental protection disposal is high, which exceeds the value of the urea-formaldehyde resin itself. Second, after the waste glue liquid is diluted with water, an appropriate wastewater treatment process is selected for treatment. This treatment method requires enterprises to have relevant equipment and the cost of wastewater treatment is relatively high. Therefore, the problem of waste rubber treatment in wood-based panel enterprises is an urgent problem that affects the production efficiency of enterprises and environmental protection.

[0003] There are no reports on the recycling technology of urea-formaldehyde resin waste glue liquid abroad, and there is also little research in China. Yao Rongjian invented a process method and coating technology for reinforcing paperboard using waste glue, but it is only used in the production of reinforced corrugated paperboard. Yu Wenji used Fourier transform infrared spectroscopy to study the distribution and activity of solidified urea-formaldehyde resin in waste particleboard, indicating that urea-formaldehyde resin has active groups with gluing function, but did not explore the application of active groups in recycled adhesives at the same time. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a method for preparing a urea-based phenolic resin based on depolymerization of urea-formaldehyde waste rubber and its application.

[0005] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is:

[0006] On the one hand, a method for preparing urea-based phenolic resin glue based on depolymerization of urea-formaldehyde waste rubber is provided, which comprises the following steps: pre-treating the urea-formaldehyde waste rubber and then depolymerizing and reactivating it to obtain a waste rubber hydrolyzate; and adding the waste rubber hydrolyzate during the synthesis of phenolic resin to prepare urea-based phenolic resin.

[0007] Furthermore, the pretreatment of urea-formaldehyde waste rubber specifically includes the following sub-steps:

[0008] (1) Classification of waste urea-formaldehyde resin: Collect the waste urea-formaldehyde resin in a container, add an appropriate amount of water and stir to make it in a fluid state, perform graded precipitation treatment, and extract the waste urea-formaldehyde resin at the bottom as the test raw material;

[0009] (2) Neutralization treatment of urea-formaldehyde waste rubber: adding 0.1-3% of sodium hydroxide or sodium bicarbonate or a mixed neutralizer to adjust the pH value to 7.2-8.8;

[0010] (3) Grinding of urea-formaldehyde waste rubber: Grind the urea-formaldehyde waste rubber by wet or dry method, wet grinding to micron level, and naturally drying or artificially drying the waste rubber to within 100-200 mesh.

[0011] Furthermore, in step (2), the pH value is 7.5-8.5.

[0012] Furthermore, the depolymerization and reactivation treatment is specifically as follows: hydrogen peroxide or formaldehyde is mixed with urea-formaldehyde waste rubber, and treated at 160° C. for 150 minutes.

[0013] Furthermore, the preparation process of the urea-based phenolic resin is specifically as follows: phenol, sodium hydroxide, waste rubber depolymerization liquid, and formaldehyde are added in sequence under stage-by-stage temperature control to synthesize the phenolic resin in three steps, and the material is discharged when the viscosity reaches 200 mPa·s.

[0014] Furthermore, urea-formaldehyde resin slurry is added as a raw material for making glue into the phenolic resin glue reaction system, and the adding ratio is 5-25%.

[0015] Furthermore, the urea-formaldehyde resin is added in an amount of 12-18%.

[0016] Furthermore, the specific steps of the three-step method are:

[0017] 1) dissolving 43 parts of sodium hydroxide in 60 parts of water, and cooling for standby use;

[0018] 2) Install the test device as required and preheat the three-necked flask to 40-45°C;

[0019] 3) Add 145 parts of pre-melted phenol into a three-necked flask, connect a condenser, start the stirrer, add the prepared sodium hydroxide solution cooled to room temperature, pay attention to control the temperature below 50°C, add 160 parts of the first formaldehyde solution, and keep it for 10 minutes;

[0020] 4) Add 86 parts of the second formaldehyde solution, and let the temperature rise by the heat release of the reaction. After the temperature stabilizes, adjust the temperature to 80°C and keep it warm for 40 minutes;

[0021] 5) Add 6 parts of the third formaldehyde solution, keep warm for 10 minutes, and heat to boiling;

[0022] 6) Cool down to 87℃, measure the viscosity every 10 minutes at this temperature, and start unloading when the viscosity is acceptable.

[0023] On the other hand, the invention provides application of urea-based phenolic resin adhesive in preparing bamboo-wood plywood.

[0024] The beneficial effects of the present invention are:

[0025] The present invention aims at the problem of treating waste urea-formaldehyde resin glue liquid, combines the actual production of artificial board products, carries out research on the reactivation process of waste glue liquid to realize the resource utilization of urea-formaldehyde resin, and has certain creativity. Waste glue comes from the gluing process in the production process of plywood, technical wood and other products of artificial board production enterprises. The waste glue is activated and depolymerized through treatment processes such as pulping, and phenolic resin is added to be applied in the production of bamboo plywood to formulate a suitable artificial board production process. The present invention aims to reduce the pollution of waste glue liquid to the environment, realize the transformation of urea-formaldehyde resin waste glue into treasure and the green development of the artificial board industry. The research plan is feasible, the project has good application prospects, will generate dual economic benefits, and have good ecological and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a process flow chart of UF waste rubber depolymerization and PF synthesis in an embodiment of the present invention;

[0027] Figure 2 Schematic diagram of the influence of various factor levels on the curing speed of the resin in an embodiment of the present invention;

[0028] Figure 3 FTIR curves of urea-formaldehyde waste rubber, formaldehyde treatment residues, hydrogen peroxide treatment residues and their hydrolysis products in the embodiments of the present invention;

[0029] Figure 4 This is a schematic diagram of the GPC results of the phenolic resin added with hydrogen peroxide treatment solution in an embodiment of the present invention;

[0030] Figure 5 This is a schematic diagram of the GPC results of the phenolic resin with formaldehyde treatment solution added in the embodiment of the present invention. DETAILED DESCRIPTION

[0031] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.

[0032] Example

[0033] (1) Classification of waste urea-formaldehyde resin: Collect the waste urea-formaldehyde resin produced by the production enterprises of artificial boards such as high-tech wood and plywood in a container, add an appropriate amount of water and stir to make it in a fluid state, perform graded sedimentation treatment, and extract the waste urea-formaldehyde resin at the bottom as the test raw material.

[0034] (2) Neutralization of waste rubber solution: Add 0.1-3% sodium hydroxide or sodium bicarbonate or a mixed neutralizer to adjust the pH value of the mixed solution to 7.2-8.8, preferably 7.5-8.5.

[0035] (3) Reactivation of waste rubber liquid: The waste rubber liquid is dried, ground, depolymerized, and filtered. The waste rubber hydrolyzate is added to the phenolic resin synthesis process to prepare urea-based phenolic resin (UPF), and the performance of UPF glue is analyzed and evaluated.

[0036] Specifically, the experimental process of waste rubber depolymerization and phenolic resin synthesis is as follows:

[0037] 1 Experimental part

[0038] 1.1 Materials and Instruments

[0039] Phenol, formaldehyde (37% aqueous solution), and hydrogen peroxide are all industrial products; sodium hydroxide is of analytical grade; potassium bromide crystals are commercial products; urea-formaldehyde resin solid waste is collected from the waste liquid generated in the processes of veneer gluing, equipment cleaning, and process adjustment during the technological wood assembly and molding process of Maoyou Timber Co., Ltd., and is subjected to graded precipitation, neutralization and deodorization, pulping and filtration, performance testing, and natural drying to light gray powder.

[0040] YF-111B high-speed crusher; reaction kettle, 101A-1 electric heating blast dryer; Thermo Fisher Scientific Nicolet iS20 Fourier transform infrared spectrometer from the United States; Bruker Avance NEO 500MHz nuclear magnetic resonance spectrometer from Germany; TASDT Q600 synchronous thermal analyzer from the United States; Agilent PL-GPC220GPC gel permeation chromatograph from the United States; HH-2 digital display constant temperature water bath; gel making device; NDJ-8S rotational viscometer.

[0041] 1.2UF waste rubber depolymerization treatment

[0042] like Figure 1, grind the UF waste rubber to 100-200 mesh, and use KBR tablet method to measure the molecular structure of waste rubber powder by infrared. Add 5-15ml of formaldehyde solution, hydrogen peroxide and reference sample water, 1g of waste rubber powder and 30ml of water into a PTFE tank, put it into a steel kettle, seal it, heat it to 120-160℃ in an electric blast dryer, and keep it warm for 120-180m. Take it out and filter it after natural cooling, and measure and analyze the depolymerization effect by IFTR.

[0043] The mass of UF waste rubber before depolymerization is M0, and the absolute dry mass of filter paper is M ⅰ , the absolute dry mass of the filter paper and the residue is M ⅱ , calculate the percentage of waste rubber depolymerization efficiency (R DP ).

[0044]

[0045] 1.3PF resin synthesis

[0046] according to Figure 1 After the glue making device is connected, phenol, sodium hydroxide, waste glue depolymerization liquid and formaldehyde are added in sequence under segmented temperature control to synthesize phenolic resin in three steps. The material is discharged when the viscosity reaches 200mPa·s.

[0047] Specifically, the urea-formaldehyde resin slurry is added as a filler to the phenolic resin glue in a proportion of 5-25%. For comparison, a proportion of 12-18% is preferred.

[0048] The specific steps of the three-step method are:

[0049] 1) 43g sodium hydroxide was dissolved in 60g water and cooled for standby use:

[0050] 2) Install the test device as required and preheat the three-necked flask to 40-45°C;

[0051] 3) Add 145g (about 145ml) of pre-melted phenol into a three-necked flask, connect a condenser, start the stirrer, add the prepared sodium hydroxide solution cooled to room temperature, pay attention to control the temperature below 50°C, add 160g of the first formaldehyde solution, and keep it for 10 minutes (the temperature should not exceed 80°C at this time);

[0052] 4) Add 86g of the second formaldehyde solution (the temperature is controlled at 70℃~75℃ before adding), and the temperature rises by the exothermic reaction itself (the temperature is controlled below 80℃ at this time). After the temperature stabilizes, adjust the temperature to about 80℃ and keep it warm for 40 minutes;

[0053] 5) Add 6 g of formaldehyde solution for the third time, keep warm for 10 minutes (80°C), and heat to boiling (heat in a water bath for about 15 minutes);

[0054] 6) Cool down to about 87℃, and measure the viscosity every 10 minutes at this temperature. When the viscosity is qualified, the material can be unloaded (Tu-4 cup up to 35s or rotary viscometer CP = 180-200mPa·s).

[0055] *Viscosity measurement:

[0056] During the process of solidification, the inverted bubble method is generally used to control the viscosity of the reaction. The determination method is: use a test tube with a length of 100mm and an inner diameter of 9mm, put the test glue in the test tube, and control the number of seconds of inverted bubble flow to 6-8 seconds (temperature 20℃), generally controlled to more than 4 seconds. It can also be measured by using a coating-4 cup, and the number of seconds is controlled between 100-127 seconds (20C). It can also be measured by a rotating viscometer, and an Ostwald viscometer with a capillary pore size of 3mm (20℃), and the measurement seconds are about 25-30 seconds.

[0057] 1.4PF resin basic performance test

[0058] It mainly includes tests on the appearance characteristics, solid content, pH value, etc. of the resin. The test method is based on the relevant requirements of GB / T14074-2017 "Test Methods for Wood Adhesives and Their Resins".

[0059] 1.5 Plywood and bamboo-wood composite container bottom board manufacturing

[0060] The mixed slurry is added as an additive to phenolic resin glue and used in the manufacture of plywood and bamboo-wood composite container bottom board. Three sheets of hot-pressed 7-layer plywood and 21-layer wooden box board are used, and the glue ratio is as specified in Table 1. The selected glue coating and hot pressing process is glue coating amount: 400g / cm 2 ;Hot pressing temperature: 130℃;Hot pressing / holding time: 15min;Hot pressing pressure: 16kg / cm 2 The effect of adding mixed slurry (addition amount 8%) on the bonding performance of phenolic resin was analyzed, and the addition ratio of mixed slurry was adjusted. It was applied to the processing of 21-layer wooden box boards to further determine its feasibility in the production of plywood for container bottom plates. The gluing and hot pressing process is as follows: Gluing amount: 400g / cm 2 ;Hot pressing temperature: 135℃;Hot pressing / holding time: 35min;Hot pressing pressure: 20kg / cm 2 . Refer to the performance requirements of plywood in GB / T 9846-2015 to test the bonding strength and immersion peeling performance.

[0061] Table 1 Mixed slurry glue ratio for plywood

[0062]

[0063] After determining that the phenolic resin with mixed slurry is applied to the wood plywood processing process, it is further applied to the industrial production of plywood for bamboo-wood composite container bottom plates, and the appropriate mixed slurry addition ratio is determined. According to Table 2, 4 addition ratios are selected for adhesive preparation. The currently commonly used 21-layer bamboo-wood composite container bottom plate plywood assembly structure is adopted. The gluing and hot pressing process is: Glue coating amount: 400g / cm 2 ;Hot pressing temperature: 135℃;Hot pressing / holding time: 40min;Hot pressing pressure: 30kg / cm 2 , using cold in and cold out process. According to GB / T 19536-2015 requirements, elastic modulus, static bending strength, short span shear force, concentrated load, immersion stripping performance are tested.

[0064] Table 2 Glue mixing ratio of plywood mixed slurry for bamboo-wood composite container bottom plate

[0065]

[0066] 2 Results and discussion

[0067] 2.1 Effect of depolymerization process on the effect

[0068] Table 3 Analysis of the range of depolymerization rate caused by process factors

[0069]

[0070] As can be seen from the table, the range of each factor is arranged as A>B>C>D. The influence of the treatment process on the depolymerization effect is as follows: treatment liquid type>treatment liquid dosage>reaction temperature>reaction time. The trend of the influence of different levels of each factor on the depolymerization effect is as follows Figure 2 .Depend on Figure 2 It can be seen that among the selected treatment liquids, the effect of pure water thermal treatment lags far behind H2O2 and CH2O compared with the control sample. The amount of treatment liquid also has a significant effect on the depolymerization effect of UF, but after reaching a certain proportion, although the activation rate is no longer significantly improved, through the analysis of the hydrolyzate, it is found that it is of great significance for the treatment of industrial waste in the environmental protection industry, and further in-depth research will be carried out in the follow-up research. As the temperature increases, there is a certain effect. With the passage of time, the activation rate has a slight increase, but it also conforms to the principle of marginal effect. Therefore, the optimal treatment process is A1B2C3D2, that is, 10 ml of hydrogen peroxide is treated at 160°C for 150 minutes.

[0071] Analysis of infrared results of depolymerization effect Figure 3 As shown. Figure 3 It can be seen that 1036cm -1At 1136 cm, the relative intensity of linear methylene bonds (NCN) in hydrogen peroxide-treated liquid and formaldehyde-treated liquid decreased or even disappeared, indicating that hydrogen peroxide degradation is the destruction of methylene bond structure. -1 As the hydrolysis reaction proceeded, the relative intensity decreased significantly, and the branched ether bonds and linear ether bonds were destroyed to varying degrees. -1 The relative intensities of -OH and -NH- at 1388 cm-1 increased significantly, indicating that the hydrolysis reaction was quite complete. -1 The relative intensity at is significantly enhanced, indicating that more UF branches are separated from the cross-linking system. Therefore, hydrogen peroxide can effectively destroy the methylene bonding structure, thus having a better degradation effect.

[0072] Performance analysis of the regenerated phenolic resin: Its basic performance, viscosity, appearance, etc. are all good, and the viscosity is at a low level. GPC results: The average molecular weight of the phenolic resin treated with hydrogen peroxide and formaldehyde is 34746 and 21935.

[0073] 2.2 Plywood test results

[0074] According to the requirements of the Class I plywood bonding strength and immersion peeling test standard in GB / T 9846-2015, the 7-layer plywood and 21-layer wooden boxboard were subjected to boiling water circulation cooking treatment test. Table 4 shows the test results of the bonding strength and wood breakage rate of the 7-layer plywood.

[0075] Table 4 Test results of bonding strength and wood breakage rate of 7-layer plywood

[0076] Performance Indicators Number of test pieces Mean Standard Deviation Glue strength 18 1.80MPa 0.29 Wood breakage rate 18 63.57% 41.44

[0077] According to the standard, the bonding strength of Class I and Class II plywood processed with poplar, birch and Masson pine veneers should be greater than 1.0MPa. The test results show that the average bonding strength of 7-layer plywood processed with phenolic resin with 8% mixed slurry is 1.80MPa, which is higher than the standard value, and the average wood breakage rate reaches 63.57%.

[0078] The plywood immersion peeling performance was further tested. After circulating boiling water and drying, there was no peeling between the layers of the test piece. The national standard requires that the continuous delamination length of one side of the test piece should not exceed 25mm, which shows that its immersion peeling performance can meet the standard requirements.

[0079] The performance test results show that when the mixed slurry addition amount is 8%, the performance of phenolic resin can meet the bonding strength requirements of Class I plywood. In order to explore its feasibility for industrial production of plywood for container bottom plates, the bonding strength and wood breakage rate of 21 layers of wooden box boards were tested when the mixed slurry addition amount was 15%. The results show (Table 5) that its bonding strength and wood breakage rate can also meet the requirements of Class I plywood. It can be seen that when the mixed slurry addition ratio increases from 8% to 15%, the number of plywood layers increases from 7 to 21 layers, the performance of the adhesive is not affected, and the bonding strength can meet the product quality requirements. Referring to the Class I immersion and peeling test method for plywood, its immersion and peeling performance was tested and it was found that there was no stratification and peeling phenomenon in the specimen, indicating that the phenolic resin after adding the mixed slurry has good water resistance.

[0080] Table 5 Test results of bonding strength and wood breakage rate of 21-layer wooden boxboard

[0081] Performance Indicators Number of test pieces Mean Standard Deviation variance Glue strength 18 2.01 0.29 0.08 Wood breakage rate 18 72.14 21.90 479.67

[0082] 2.3 Test results of plywood for bamboo-wood composite container bottom

[0083] The test results of 7-layer plywood and 21-layer wooden boxboards show that after adding mixed slurry to phenolic resin, the bonding strength and water resistance can meet the product quality requirements. At present, plywood for container bottom plates generally adopts bamboo-wood composite structure, that is, bamboo units such as bamboo curtains and bamboo mats are glued with wooden veneers to form a multi-layer composite structure. In the process of bamboo and wood composite, due to the dense structure of bamboo and worse permeability than wood, higher requirements are placed on adhesives to obtain good bamboo-wood composite interface bonding performance. In order to promote the application of phenolic resin with mixed slurry added to the production of plywood for bamboo-wood composite container bottom plates, the performance of bamboo-wood composite boxboards processed with phenolic resin with different amounts of mixed slurry added was tested.

[0084] Table 6 shows the performance test results of bamboo-wood composite boxboard under the conditions of mixed slurry mixing ratio of 8%, 12%, 18% and 25%. According to the requirements of GB / T 19536-2015 "Plywood for container bottom plate", the longitudinal and transverse elastic modulus should be no less than 10000MPa and 3500MPa respectively, the longitudinal and transverse static bending strength should be no less than 85MPa and 35MPa respectively, the short span shear force should be no less than 6900N, and the concentrated load should be no less than 48KN. When the mixed slurry addition ratio is less than 25%, the physical and mechanical properties such as longitudinal and transverse elastic modulus and static bending strength are higher than the standard requirements. It can be seen that the performance of phenolic resin with mixed slurry can meet the production requirements of bamboo-wood composite container bottom plates.

[0085] Table 6 Performance test results of bamboo-wood composite container bottom plate

[0086]

[0087] In the urea-formaldehyde resin mixed slurry, its main components are water, urea-formaldehyde resin, fillers (such as flour) and calcium oxide, sodium hydroxide, potassium hydroxide, tea polyphenols, eucalyptus oil and other substances added in the later mixed slurry processing. In the wood-based panel industry, the addition of fillers in adhesives can increase the viscosity of adhesives, improve the adhesion of adhesives on the surface of materials, reduce the brittleness of the adhesive layer, and improve the bonding strength; but too much filler will make the viscosity of the adhesive too high, which is not easy to flow and spread the adhesive layer, and reduce the bonding strength. Adding the mixed slurry to the phenolic resin as an adhesive auxiliary material, while ensuring the performance of the adhesive, realizes the resource recycling of urea-formaldehyde resin waste glue. Taking the longitudinal static bending strength of the bamboo-wood composite container bottom plate as an example, it can be seen from the experimental results that when the mixed slurry addition ratio is 8%, the longitudinal static bending strength of the product is slightly higher than that of the control sample. When the addition amount is 12% and 18%, the performance is equivalent to the control sample. However, when the addition amount is increased to 25%, its static bending strength decreases significantly. Therefore, when utilizing urea-formaldehyde resin waste glue liquid, in order to ensure product quality, the mixing slurry addition ratio should be 12-18%.

[0088] The reactivation mechanism is the core of the reuse of waste urea-formaldehyde resin. Only after activation, the active groups of waste urea-formaldehyde resin are generated or stimulated to participate in the curing reaction of artificial board molding again. In the urea-formaldehyde-phenolic resin system, the key difference between the addition of urea-formaldehyde and ordinary fillers is that urea-formaldehyde resin participates in the curing reaction during curing, so as to ensure the bonding strength and mechanical properties of the product while reducing the amount of glue used. The present invention is the first domestic and foreign reactivation treatment process for waste urea-formaldehyde resin and explores the synergistic bonding mechanism of reactivated urea-formaldehyde resin waste glue and phenolic resin.

[0089] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0090] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing urea-based phenolic resin glue based on depolymerization of urea-formaldehyde waste rubber, characterized in that: The following steps are involved: The urea-formaldehyde waste rubber is pre-treated and then depolymerized and reactivated to obtain a waste rubber hydrolyzate; The urea-based phenolic resin is prepared by adding waste rubber hydrolyzate during the synthesis of phenolic resin.

2. The method for preparing urea-based phenolic resin adhesive based on depolymerization of urea-formaldehyde waste rubber according to claim 1, characterized in that: Urea-formaldehyde waste rubber pretreatment specifically includes the following sub-steps: (1) Classification of waste urea-formaldehyde resin: Collect the waste urea-formaldehyde resin in a container, add an appropriate amount of water and stir to make it in a fluid state, perform graded precipitation treatment, and extract the waste urea-formaldehyde resin at the bottom as the test raw material; (2) Neutralization treatment of urea-formaldehyde waste rubber: adding 0.1-3% of sodium hydroxide or sodium bicarbonate or a mixed neutralizer to adjust the pH value to 7.2-8.8; (3) Grinding of urea-formaldehyde waste rubber: Grind the urea-formaldehyde waste rubber by wet or dry method, wet grinding to micron level, and naturally drying or artificially drying the waste rubber to within 100-200 mesh.

3. The method for preparing urea-based phenolic resin adhesive based on depolymerization of urea-formaldehyde waste rubber according to claim 2, characterized in that: In step (2), the pH value is 7.5 to 8.

5.

4. The method for preparing urea-based phenolic resin adhesive based on depolymerization of urea-formaldehyde waste rubber according to claim 1, characterized in that: The depolymerization and reactivation treatment is specifically as follows: hydrogen peroxide or formaldehyde is mixed with urea-formaldehyde waste rubber and treated at 160°C for 150 minutes.

5. The method for preparing urea-based phenolic resin adhesive based on depolymerization of urea-formaldehyde waste rubber according to claim 1, characterized in that: The specific preparation process of urea-based phenolic resin is as follows: phenol, sodium hydroxide, waste rubber depolymerization liquid and formaldehyde are added in sequence under stage-by-stage temperature control to synthesize phenolic resin by three-step method, and the material is discharged when the viscosity reaches 200 mPa·s.

6. The method for preparing urea-based phenolic resin adhesive based on depolymerization of urea-formaldehyde waste rubber according to claim 5, characterized in that: The urea-formaldehyde resin hydrolyzate is added into the phenol-formaldehyde resin adhesive reaction system at a ratio of 5-25%.

7. The method for preparing urea-based phenolic resin adhesive based on depolymerization of urea-formaldehyde waste rubber according to claim 6, characterized in that: The addition ratio of urea-formaldehyde resin is 12-18%.

8. The method for preparing urea-based phenolic resin adhesive based on depolymerization of urea-formaldehyde waste rubber according to claim 5, characterized in that: The specific steps of the three-step method are: 1) dissolving 43 parts of sodium hydroxide in 60 parts of sodium hydroxide and cooling for standby use; 2) Install the test device as required and preheat the three-necked flask to 40-45°C; 3) Add 145 parts of pre-melted phenol into a three-necked flask, connect a condenser, start the stirrer, add the prepared sodium hydroxide solution cooled to room temperature, pay attention to control the temperature below 50°C, add 160 parts of the first formaldehyde solution, and keep it for 10 minutes; 4) Add 86 parts of the second formaldehyde solution, and let the temperature rise by the heat release of the reaction. After the temperature stabilizes, adjust the temperature to 80°C and keep it warm for 40 minutes; 5) Add 6 parts of the third formaldehyde solution, keep warm for 10 minutes, and heat to boiling; 6) Cool down to 87℃, measure the viscosity every 10 minutes at this temperature, and start unloading when the viscosity is acceptable.

9. A urea-based phenolic resin adhesive prepared by the method according to any one of claims 1 to 8.

10. Use of the urea-based phenolic resin adhesive according to claim 9 in the preparation of bamboo-wood plywood.

Citation Information

Cited By

  • A recycled wood composite engineered wood panel and its preparation process

    CN122666599A